Compostos indutores e genes regulando a expressão da bomba de efluxo Tap em Mycobacterium bovis BCG - Felix, Carolina Rodrigues (2013)
Transport proteins related to drug efflux play an important role not only in the acquisition of drug-resistant phenotypes, but also in virulence of M. tuberculosis. The main objective of this study was to analyze the regulation of genes encoding the protein Rv1258c Tap considering the expression of genes Rv1255c and Rv1257c. RNA was extracted from cultures of M. bovis BCG overexpressing Rv1255c and Rv1257c, as well as a control strain containing the vector pVV16, and qRT-PCR of the Rv1258c gene was performed. RT-PCR was performed using RNA isolated previously from M. tuberculosis CDC1551, in order to verify that Rv1255c, Rv1256c, Rv1257c and Rv1258c genes are all connected to a transcript. The strain M. bovis BCG, expressing a red fluorescent protein under control of the promoter Rv1258c (pVVTapPro) was grown in the presence of streptomycin and glycine to verify the induction of the promoter. The qRT-PCR showed a downregulation of the gene in the strain overexpressing Rv1258c and Rv1257c, but no difference was observed in the strain overexpressing Rv1255c compared with the control. An increase in fluorescence was observed in the strain containing the promoter of the tap in the presence of 1 mg/L of streptomycin in comparison with the control. A two-fold induction of gene Tap was also observed in the presence of 1.6 mM glycine. The results suggest a role for Rv1257c in the regulation Tap expression. Moreover, the induction of Tap by streptomycin supports the importance of this protein in multidrugresistant M. tuberculosis. The effect of glycine on Tap promoter suggest a physiological role in cellular detoxification for this efflux pump. In conclusion, this study reinforces the need to obtain a deeper knowledge about the Tap protein operon and its regulation, in order to assist in the development of inhibitors of this efflux pump and possibly other mechanisms of induced resistance.